Consuming colonial nostalgia in Kolkata, India - Bandyopadhyay, Ranjan (Annals of tourism research, 2022)
Imperialist nostalgia has been well documented by tourism scholars; however colonial nostalgia has been ignored as this is, arguably, considered embarrassing. This ethnography, utilizing Homi Bhabha's (1994) concepts of hybridity and mimicry, was conducted with young Indian domestic tourists visiting postcolonial Kolkata, India. Findings revealed that despite the current Indian government's efforts to wipe away the colonial legacy, many young Indians have no qualms about carrying on the legacy of the British Raj. Nostalgia for these young Indian tourists is rooted in an imagined sense of the past and born out of frustration with the present and the uncertainty of the future. The private sector in the tourism industry in India, capitalizing on this trend, increasingly lures domestic tourists. •Scholars have studied imperialist nostalgia but ignored colonial nostalgia.•This ethnography explores how colonial nostalgia plays out in Kolkata.•Utilizes Homi Bhabha's (1994) concepts of hybridity and mimicry.•Many young Indians have no qualms about carrying on the legacy of the British Raj.